Mechanical properties of carbon nanotubes-modified epoxy grout for pipeline repair system - Hanis Hazirah, Arifin; Nurfarahin, Zainal; Libriati, Zardasti; Nordin, Yahaya; Lim, Kar Sing; Norhazilan, Md Noor (Penerbit Universiti Teknologi Malaysia, 2019)
Epoxy grout properties are theoretically important in predicting the behaviour of the composite pipeline repair system. Usually, it is used as an infill material to fill the gap or irregularity on the surface caused by pipe corrosion and ensures a smooth bed before fibre wrapper can be applied to recover the pipeline strength. In this research, the existing commercially available epoxy resin grout has been strengthened by using Carbon Nanotubes (CNTs) at the amount 0.1% of weight fractional to evaluate their apropos behaviour to the neat epoxy grout. The various mechanical tests were performed on this modified grout to identify its compression, tensile, flexural and lap shear strength. In addition, the dispersion process of CNTs was carried out by using ultrasonication and three-roll mill technique to ensure an optimum enhancement in the properties of the polymer matrix. By comparing the strength, 0.1% of CNTs filler has significantly improved the strength of grout in flexural, tensile and shear bonding but not in compression. In addition, the results also indicate that CNTs filler has increased the modulus of elasticity of the infill material. Therefore, it demonstrates the intrinsic potential of the CNTs in modifying the properties of the epoxy grout.